1999
DOI: 10.1191/096032799678840273
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of survival capacity in heat shocked cells by subsequent exposure to minute amounts of chemical stressors; role of similarity in hsp-inducing effects

Abstract: 1 A brief and moderate heat shock to Reuber H35 hepatoma cells causes a rapid increase in the synthesis of heat shock proteins (hsp) and initiates the development of thermotolerance, which results in an increased ability to survive exposure to otherwise lethal temperatures. 2 We now demonstrate that low doses of various chemical stressors (arsenite, cadmium, mercury, lead, copper, menadione and diethyldithiocarbamate (ddtc)), at concentrations that do not exert any effect in control cultures, are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…Another study added that chemical stressors such as arsenite, cadmium, mercury, lead, copper, menadione and diethyldithiocarbamate were able to enhance the synthesis of heat shock proteins (HSPS) and stimulate the development of thermotolerance when applied to Reuber H35 hepatoma cells culture. They also, concluded that low doses of toxic compounds may have beneficial effects related to the stimulation of endogenous cytoprotective mechanisms (29). These explanations are in agreement with our findings that the appearance of this new protein (100 KDa) may function as a stress protein due to the action of Cu(II) complex or may be a modified expression of some intoxicated gene by Cu(II) complex.…”
Section: Discussionsupporting
confidence: 82%
“…Another study added that chemical stressors such as arsenite, cadmium, mercury, lead, copper, menadione and diethyldithiocarbamate were able to enhance the synthesis of heat shock proteins (HSPS) and stimulate the development of thermotolerance when applied to Reuber H35 hepatoma cells culture. They also, concluded that low doses of toxic compounds may have beneficial effects related to the stimulation of endogenous cytoprotective mechanisms (29). These explanations are in agreement with our findings that the appearance of this new protein (100 KDa) may function as a stress protein due to the action of Cu(II) complex or may be a modified expression of some intoxicated gene by Cu(II) complex.…”
Section: Discussionsupporting
confidence: 82%
“…Our recent studies have shown interesting consequences of this period of increased sensitivity for Hsp synthesis and development of tolerance. When low doses of physical or chemical stressors are applied during this sensitive period following a more vigorous stress, survival capacity and the synthesis of heat shock proteins were enhanced [12][13][14][15][16]. This stimulation was observed at low doses of stress conditions that alone could not induce Hsp synthesis.…”
Section: Introductionmentioning
confidence: 85%
“…In a variation of the costress strategy described above Wiegant and co-workers (19) found that a mild heat shock makes cells more susceptible to a second weak stressor like very small concentrations of chemicals (arsenite, various heavy metals, menadione or diethyldithiocarbamate). The weak stressor which by itself does not provoke a heat shock response is then able to stimulate stress tolerance of the cells…”
Section: Exploiting Stress Resistancementioning
confidence: 97%